A quaternary ammonium xylan coated mercury ion detection paper-based chip and its preparation method and application

By uniformly loading the quaternized xylan coating of gold and silver nanoparticles and Raman beacon molecules on the surface of the paper, the specific reaction of quaternized xylan and mercury ions is solved in the prior art heavy metal ion detection is solved by using the specific reaction of quaternized xylan and mercury ions. The sensitivity and cost issues have achieved high sensitivity and quantitative detection of mercury ion.

CN118847241BActive Publication Date: 2025-02-11SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411328017.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-11
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The prior art is difficult to achieve rapid, low-cost and high-sensitivity quantitative detection of heavy metal ions, especially in remote areas and on-site monitoring, and there is a lack of applicable detection methods.

Method used

Using quaternized xylan as a stabilizer and binder, gold and silver nanoparticles and Raman beacon molecules are uniformly loaded on the surface of the paper, and Raman is enhanced by the specific reaction of quaternized xylan with mercury ions. Signal to realize high sensitivity detection of mercury ions.

Benefits of technology

It realizes high sensitivity and quantitative detection of mercury ions, which has the advantages of low cost, simple preparation, green and environmentally friendly, and can conduct on-site monitoring in remote areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847241B_ABST
    Figure CN118847241B_ABST
Patent Text Reader

Abstract

The present invention relates to a quaternary ammonium xylan coating mercury ion detection paper-based chip and its preparation method and application. The preparation method comprises: quaternary ammonium xylan is modified to obtain quaternary ammonium xylan, and gold nanoparticles are prepared using the quaternary ammonium xylan as a reducing agent, and then Raman beacon molecules are added to the system to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material; the composite coating material is applied to the surface of paper, and then immersed in a silver ion solution to utilize the reducing property of the quaternary ammonium xylan to in-situ reduce the silver ions to silver nanoparticles deposited on the coating surface, thereby obtaining a quaternary ammonium xylan coating mercury ion detection paper-based chip. The present invention utilizes the chloride ions loaded by the quaternary ammonium group on the quaternary ammonium xylan to react specifically with mercury ions, and proportionally interfere with the Raman signal, thereby achieving the effect of high sensitivity and quantitative detection of mercury ions, and also has the advantages of mild preparation conditions and environmentally friendly preparation raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of food and environment detection and biomass resource utilization, and specifically relates to a quaternized xylan-coated mercury ion detection paper-based chip and a preparation method and application thereof. Background Art

[0002] Traditional methods for detecting heavy metals include atomic absorption spectroscopy, atomic fluorescence spectroscopy, inductively coupled plasma mass spectrometry, etc. Although these methods have high sensitivity, reliability and accuracy, the instrument price and maintenance cost are high, lack of portability, and require high technical skills of the detection personnel and are time-consuming. They are difficult to popularize in remote areas that are in urgent need of heavy metal pollution detection, and long-distance delivery cannot meet the needs of on-site monitoring and the timeliness of fresh product detection. At present, the technology of rapid, low-cost, and highly sensitive quantitative or semi-quantitative detection of heavy metal content is in a state of lack, which has become a bottleneck problem restricting the implementation of stricter supervision of heavy metal pollutant residues.

[0003] Surface enhanced Raman scattering (SERS) technology is one of the most promising technologies for rapid detection of trace pollutants. Its detection principle is to form a SERS active substrate in the form of rough metal surfaces, nanoparticle aggregation or array elements such as gold, silver, and copper, and generate a strong electromagnetic field through the localized surface plasmon resonance excited by the surface of metal nanoparticles to achieve Raman signal enhancement, with an enhancement range of 4-7 orders of magnitude. Paper-based chips based on SERS technology have high sensitivity and fast response, and have attracted the attention of researchers in recent years in the detection of food pollutants, agricultural product pollutants, and water and soil pollutants. However, heavy metal ions are different from organic harmful chemicals and do not have Raman activity. Therefore, functionalizing the SERS substrate to detect heavy metal ions has become the key research direction of SERS detection of heavy metal ions. Summary of the invention

[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a quaternary ammonium xylan coated mercury ion detection paper-based chip. The present invention uses quaternary ammonium xylan to reduce gold and silver ions to obtain a gold-silver nanoparticle dispersion, and the quaternary ammonium xylan and the gold-silver nanoparticle mixed dispersion are coated on the surface of paper to prepare a quaternary ammonium xylan coated SERS paper-based chip. The excess chloride ions carried by the quaternary ammonium xylan can react specifically with mercury ions. As the concentration of mercury ions in the test liquid increases, the Raman signal is proportionally enhanced, thereby achieving high-sensitivity and quantitative detection of mercury ion pollutants.

[0005] Another object of the present invention is to provide a quaternary ammonium xylan coated mercury ion detection paper-based chip prepared by the above method. The quaternary ammonium xylan coated mercury ion detection paper-based chip has the functions of high sensitivity and quantitative detection of mercury ion pollutants, and also has the advantages of simple preparation and low cost.

[0006] Another object of the present invention is to provide the use of the quaternized xylan-coated mercury ion detection paper-based chip.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a quaternized xylan-coated mercury ion detection paper-based chip comprises the following steps:

[0009] (1) A quaternary ammonium xylan solution and an aqueous solution of tetrachloroauric acid trihydrate (HAuCl4·3H2O) are mixed and reacted to obtain a quaternary ammonium xylan / gold nanoparticle dispersion; Raman beacon molecules are added to the quaternary ammonium xylan / gold nanoparticle dispersion to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material;

[0010] (2) coating the quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared in step (1) onto the surface of paper to prepare quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper;

[0011] (3) Immersing the quaternary ammonium xylan / gold nanoparticle / beacon molecule composite coated paper prepared in step (2) into a silver ion solution for reaction, further utilizing the reducing property of the quaternary ammonium xylan to in situ reduce the silver ions to silver nanoparticles deposited on the coating surface, taking out and drying, thereby obtaining a quaternary ammonium xylan coated mercury ion detection paper-based chip.

[0012] Preferably, the quaternized xylan in the quaternized xylan solution in step (1) is prepared by the following steps: xylan and a quaternizing agent are reacted at 30-60°C and a pH of 8-12 for 12-24 hours to obtain quaternized xylan; the molar ratio of the xylan to the quaternizing agent is 1:1-1:1.5.

[0013] More preferably, the xylan is extracted from wood fiber raw materials; the wood fiber raw materials include at least one of hardwood, corn cobs, bagasse, crop straw, bamboo, grain husks, and oil tea fruit shells.

[0014] More preferably, the quaternizing agent is one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, dodecyltrimethylammonium chloride, tetrabutylammonium chloride and the like.

[0015] Preferably, in step (1), the quaternary ammonium xylan solution is mixed with an aqueous solution of tetrachloroauric acid trihydrate (HAuCl4·3H2O), and then reacted at 40-90°C for 10-80 min to obtain a quaternary ammonium xylan / gold nanoparticle dispersion.

[0016] More preferably, the mass ratio of the tetrachloroauric acid trihydrate to the quaternary ammonium xylan in the quaternary ammonium xylan solution is 5-40 mg: 0.1-2 g.

[0017] Preferably, the Raman beacon molecule in step (1) is at least one of 4-thiobenzoic acid (4-MBA), crystal violet (CV), and rhodamine 6G (R6G).

[0018] More preferably, the solution system used to dissolve the Raman beacon molecules is at least one of water, methanol-chloroform, and anhydrous ethanol; and the concentration of the Raman beacon molecule solution is 10-100 mmol / L.

[0019] Preferably, in step (1), the mass ratio of the Raman beacon molecule to tetrachloroauric acid trihydrate is 0.2-5:5-40.

[0020] Preferably, in step (1), the Raman beacon molecule is added to the quaternized xylan / gold nanoparticle dispersion and reacted at 30-60° C. for 10-60 min.

[0021] Preferably, in step (2), the method used to apply the quaternized xylan / gold nanoparticle / beacon molecule composite coating material to the paper surface is at least one of roller coating, spin coating, spray coating, dipping, and chemical vapor deposition.

[0022] More preferably, in step (2), the coating treatment of the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating material on the surface of the paper is double-sided coating, 5 to 10 times on each side; the effective loading amount of the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating material on the paper is 5 to 10 g / m 2 .

[0023] More preferably, after each coating treatment in step (2), the coated paper is dried in an oven for 10 to 30 min before the next coating treatment. After all coating treatments are completed, the coated paper is placed in a vacuum drying oven for 12 to 24 h.

[0024] Preferably, the specific steps of step (3) are: placing the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coated paper into a silver ion solution at 50-80°C for reaction for 30-60 min, and then vacuum drying the treated test paper at 45-55°C for 12-24 h.

[0025] More preferably, the silver ion solution is Tollens reagent, which is prepared by mixing 0.5-5 mL of 1-4 wt% sodium hydroxide solution and 0.6-1.5 mL of 0.01-0.1 mol / L silver nitrate solution, and then adding ammonia water until the precipitate just disappears.

[0026] The quaternary ammonium xylan coated mercury ion detection paper-based chip prepared by the method of the present invention uses quaternary ammonium xylan as a stabilizer and adhesive to effectively and evenly load gold and silver nanoparticles and Raman beacon molecules on the surface of paper.

[0027] Xylan is a natural polymer with abundant reserves, good biocompatibility and biodegradability. Because it contains abundant reducing functional groups, unique rheological properties in water and good water dispersibility, it has great potential as a reducing agent and stabilizer for metal nanoparticles. Compared with other reducing agents, xylan is more environmentally friendly and does not require the addition of additional stabilizers. More importantly, xylan contains abundant hydroxyl groups and can be functionalized. Therefore, the present invention introduces chloride ions into its molecular chain to obtain quaternized xylan, which retains the good dispersibility and reducibility of xylan while enabling it to obtain specific reaction ability with heavy metal ions, interfere with SERS signals, and thus achieve high sensitivity and high selectivity detection of heavy metal cations by SERS technology.

[0028] The quaternary ammonium xylan coated mercury ion detection paper-based chip prepared by the present invention can be used to detect mercury ions in a solution. The quaternary ammonium xylan coated mercury ion detection paper-based chip prepared by the present invention can achieve high sensitivity and quantitative detection of mercury ion pollutants without the need to add additional stabilizers, and is low-cost and green and environmentally friendly.

[0029] Specifically, the detection step includes:

[0030] (1) Establishing the Raman signal standard curve of the quaternary ammonium xylan-coated mercury ion detection paper-based chip using a standard mercury ion solution;

[0031] (2) Drop the test solution containing mercury ions onto the quaternary ammonium xylan coated mercury ion detection paper-based chip. The chloride ions carried by the quaternary ammonium xylan react with the mercury ions to enhance the Raman signal, and the quantitative detection of mercury ions can be achieved through the Raman spectrometer.

[0032] Preferably, the mercury ion concentration of the test solution is 1×10 -5 ~1×10 -15 mol / L.

[0033] Preferably, the wavelength of the light source of the Raman spectrometer used in the mercury ion detection process is any one of 532 nm, 633 nm, and 785 nm.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0035] (1) The quaternized xylan-coated mercury ion detection paper-based chip of the present invention has high detection sensitivity, fast response, and can achieve quantitative detection. At the same time, xylan has a natural affinity with paper, which can effectively anchor the SERS substrate to the surface of paper and has better durability.

[0036] (2) The method for preparing the quaternary ammonium xylan coated mercury ion detection paper-based chip of the present invention has the advantages of simple process, mild preparation conditions, green and degradable, and no need to add additional stabilizers. At the same time, the method for preparing gold and silver nanoparticles by reduction using quaternary ammonium xylan can efficiently and stably reduce tetrachloroauric acid trihydrate to form gold nanoparticles; and can assist in the reduction of silver nitrate to obtain silver nanoparticles.

[0037] (3) The method for preparing the quaternary ammonium xylan coated mercury ion detection paper-based chip of the present invention uses quaternary ammonium xylan that is green and degradable, environmentally friendly, simple in preparation method, and low in cost. In addition, the present invention effectively utilizes plant polysaccharide resources in pulp and paper making and agricultural and forestry biomass processing industries, and uses plant polysaccharide resources to replace expensive oligosaccharides, ribose, etc. in SERS technology, thereby reducing costs and realizing high-value utilization of plant polysaccharide resources, providing a new approach for plant polysaccharide resources and SERS technology, and having good economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The carbon nuclear magnetic resonance spectra of the quaternized xylan and the unmodified xylan used in Example 1 are shown in FIG.

[0039] Figure 2 This is the ultraviolet spectrum of the gold nanoparticle dispersion obtained by reducing quaternized xylan in Examples 1-4, where M1-M4 represent Examples 1-4, respectively.

[0040] Figure 3 The SEM image (a) and EDS images (b) to (d) of the quaternary ammonium xylan-coated mercury ion detection paper-based chip coated with the quaternary ammonium xylan / gold nanoparticle dispersion in Example 1 and treated with Tollens reagent are shown.

[0041] Figure 4 10 -15 Raman spectra of mol / L mercury ion solution and M1 and M1-0 blank controls.

[0042] Figure 5Raman spectrum of the paper-based chip M1 for mercury ion detection with quaternized xylan coating at 1589 cm -1 Fitting curve of peak intensity at and different mercury ion concentrations.

[0043] Figure 6 The Raman spectra of the quaternized xylan-coated mercury ion detection paper-based chip M2 after adding different metal ion solutions at 1589 cm -1 Peak intensity comparison diagram at . DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.

[0045] Example 1

[0046] (1) 20 g of dried dewaxed bagasse raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and a 1.5 wt% sodium hydroxide solution was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 60°C for 3 h, and the extract was precipitated with alcohol to obtain alkali-extracted bagasse xylan. The prepared xylan was reacted with 3-chloro-2-hydroxypropyltrimethylammonium chloride (molar ratio 1:1) at 40°C and pH 8.5 for 24 h for quaternization modification to obtain quaternized xylan.

[0047] A certain amount of quaternary ammonium xylan was dissolved in ultrapure water to prepare a 10 wt% quaternary ammonium xylan solution. 3 mL of the quaternary ammonium xylan solution was added to 12 mL of tetrachloroauric acid trihydrate aqueous solution containing 5 mg of tetrachloroauric acid trihydrate, and the mixture was reacted in a constant temperature water bath at 60 °C for 30 min with stirring at a speed of 300 rpm to obtain a quaternary ammonium xylan / gold nanoparticle dispersion. After the reaction, 100 μL of 10 mmol / L 4-thiobenzoic acid (4-MBA) ethanol solution was added to the quaternary ammonium xylan / gold nanoparticle dispersion and treated at 30 °C for 20 min to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0048] (2) The quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was coated on the surface of 5 cm×5 cm filter paper by roller coating, and each side was coated 10 times. After each coating, the filter paper was placed in a 45°C oven for 20 min. After coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper.

[0049] (3) Mix 2 mL of 0.2 wt% sodium hydroxide and 0.6 mL of 0.1 mol / L silver nitrate solution, then add ammonia water until the precipitate disappears to prepare Tollens reagent. The quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper prepared in step (2) was placed in the Tollens reagent and reacted at 60°C for 45 minutes. After the reaction, it was placed in a vacuum drying oven at 50°C for 12 h to obtain the quaternary ammonium xylan coated mercury ion detection paper-based chip M1. The effective loading amount of the quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material was 8.32 g / m 2 .

[0050] The configured 1.0×10 -15 10 μL of mol / L mercury ion solution was dropped onto the quaternized xylan coated mercury ion detection paper chip M1, and the Raman spectrum was collected using a 633 nm light source. The Raman spectrum of 4-MBA was observed at 1589 cm -1 There was an obvious enhancement effect at the blank sample, which was 59% higher than that of the blank sample. The mercury ion concentration was calculated by the standard curve to be 0.9×10 -15 mol / L. After the quaternary ammonium xylan coated mercury ion detection paper-based chip M1 was horizontally worn 50 times with a 100 g weight, the above mercury ion detection experiment was carried out and it was found that its performance remained unchanged.

[0051] Example 2

[0052] (1) 20 g of dried dewaxed tea shell raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and a 2 wt% sodium hydroxide solution was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 90°C for 3 h, and the extract was precipitated with alcohol to obtain alkali-extracted tea shell xylan. The prepared xylan was reacted with 3-chloro-2-hydroxypropyltrimethylammonium chloride (molar ratio 1:1.2) at 50°C and pH 8 for 12 h for quaternization modification to obtain quaternized xylan.

[0053] A certain amount of quaternary ammonium xylan was dissolved in ultrapure water to prepare a 15 wt% quaternary ammonium xylan solution, 3 mL of the quaternary ammonium xylan solution was added to 12 mL of tetrachloroauric acid trihydrate aqueous solution containing 15 mg of tetrachloroauric acid trihydrate, and the mixture was reacted in a 65 ℃ constant temperature water bath with stirring for 35 min at a stirring speed of 300 rpm to obtain a quaternary ammonium xylan / gold nanoparticle dispersion. After the reaction, 150 μL of an ethanol solution of 4-thiobenzoic acid with a concentration of 40 mmol / L was added to the quaternary ammonium xylan / gold nanoparticle dispersion and treated at 35 ℃ for 30 min to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0054] (2) The quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was coated on the surface of 5 cm×5 cm filter paper by impregnation, and impregnation was performed 5 times in total. After each impregnation, the filter paper was placed in a 60°C oven for 15 min. After the coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper.

[0055] (3) Mix 3 mL of 0.15 wt% sodium hydroxide and 0.9 mL of 0.1 mol / L silver nitrate solution, then add ammonia water until the precipitate disappears to prepare Tollens reagent. The quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper prepared in step (2) was placed in the Tollens reagent and reacted at 75°C for 30 minutes. After the reaction, it was placed in a vacuum drying oven at 50°C for 12 h to obtain the quaternary ammonium xylan coated mercury ion detection paper-based chip M2. The effective loading amount of the quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material was 8.14 g / m 2 .

[0056] The configured 1.0×10 -7 20 μL of mol / L mercury ion solution was dropped onto the quaternary ammonium xylan coated mercury ion detection paper-based chip M2, and the Raman spectrum was collected using a 532 nm light source. The Raman spectrum of 4-MBA was observed at 1589 cm -1 The mercury ion concentration was significantly enhanced, which was 30000% higher than that of the blank sample. The mercury ion concentration was calculated by the standard curve to be 1.0×10 -7 mol / L. After the quaternary ammonium xylan coated mercury ion detection paper-based chip M2 was horizontally worn 50 times with a 100 g weight, the above mercury ion detection experiment was carried out and it was found that its performance remained unchanged.

[0057] Example 3

[0058] (1) 20 g of dried dewaxed hardwood raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and anhydrous dimethyl sulfoxide was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 80°C for 7 hours, and the extract was precipitated with alcohol to obtain alkali-extracted hardwood xylan. The prepared xylan was quaternized using 2,3-epoxypropyltrimethylammonium chloride (molar ratio 1:1) at 30°C and pH 9 for 24 hours to obtain quaternized xylan.

[0059] A certain amount of quaternary ammonium xylan was dissolved in ultrapure water to prepare a 20 wt% quaternary ammonium xylan solution, 5 mL of the quaternary ammonium xylan solution was added to 10 mL of tetrachloroauric acid trihydrate aqueous solution containing 25 mg of tetrachloroauric acid trihydrate, and the mixture was reacted in a 75 ℃ constant temperature water bath with stirring for 20 min at a stirring speed of 300 rpm to obtain a quaternary ammonium xylan / gold nanoparticle dispersion. After the reaction, 200 μL of 30 mmol / L crystal violet ethanol solution was added to the quaternary ammonium xylan / gold nanoparticle dispersion and treated at 40 ℃ for 40 min to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0060] (2) The quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was coated on the surface of 5 cm×5 cm filter paper by spin coating, and the two sides were coated 10 times respectively. After each coating, the filter paper was placed in a 50°C oven for 25 min. After the coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper.

[0061] (3) Mix 5 mL of 0.3 wt% sodium hydroxide and 1.5 mL of 0.05 mol / L silver nitrate solution, and then add ammonia water until the precipitate disappears to prepare Tollens reagent. The quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper prepared in step (2) is placed in the Tollens reagent, reacted at 80°C for 40 minutes, and after the reaction is completed, placed in a vacuum drying oven at 50°C for 12 h to obtain the quaternary ammonium xylan coated mercury ion detection paper-based chip M3. The quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material has a loading capacity of 9.79 g / m 2 .

[0062] The configured 1.0×10 -1010 μL of mol / L mercury ion solution was dropped onto the quaternary ammonium xylan coated mercury ion detection paper chip M3, and Raman spectroscopy was performed using a 633 nm light source. The Raman spectrum of crystal violet was observed at 1615 cm -1 The mercury ion concentration was significantly enhanced, which was 11000% higher than that of the blank sample. The mercury ion concentration was calculated by the standard curve to be 0.98×10 -10 mol / L. After being horizontally worn 50 times with a 100 g weight, the quaternary ammonium xylan coated mercury ion detection paper-based chip M3 was subjected to the above mercury ion detection experiment and its performance remained unchanged.

[0063] Example 4

[0064] (1) 20 g of dried dewaxed corn cob raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and a 3.5 wt% sodium hydroxide solution was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 80°C for 3 h, and the extract was subjected to alcohol precipitation to obtain alkali-extracted corn cob xylan. The prepared xylan was reacted with hexadecyltrimethylammonium chloride (molar ratio of 1:1.5) at 55°C and pH 8 for 24 h for quaternization modification to obtain quaternized xylan.

[0065] A certain amount of quaternary ammonium xylan was dissolved in ultrapure water to prepare a 40 wt% quaternary ammonium xylan solution. 5 mL of the quaternary ammonium xylan solution was added to 10 mL of tetrachloroauric acid trihydrate aqueous solution containing 40 mg of tetrachloroauric acid trihydrate, and the mixture was reacted in a constant temperature water bath at 80 °C for 40 min with a stirring speed of 300 rpm to obtain a quaternary ammonium xylan / gold nanoparticle dispersion. After the reaction, 150 μL of rhodamine 6G (R6G) ethanol solution with a concentration of 25 mmol / L was added to the quaternary ammonium xylan / gold nanoparticle dispersion and treated at 55 °C for 60 min to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0066] (2) The quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was loaded on the surface of 5 cm×5 cm filter paper by chemical vapor deposition, and repeated 5 times in total. After each treatment, the filter paper was placed in a 45°C oven for 15 min. After the coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper.

[0067] (3) Mix 3.5 mL of 0.2 wt% sodium hydroxide and 1.2 mL of 0.01 mol / L silver nitrate solution, then add ammonia water until the precipitate disappears to prepare Tollens reagent. The quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper prepared in step (2) was placed in the Tollens reagent and reacted at 75°C for 50 minutes. After the reaction, it was placed in a vacuum drying oven at 50°C for 24 hours to obtain the quaternary ammonium xylan coated mercury ion detection paper-based chip M4. The effective loading amount of the quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material is 9.65 g / m 2 .

[0068] The configured 1.0×10 -12 50 μL of mol / L mercury ion solution was dropped onto the quaternary ammonium xylan coated mercury ion detection paper chip M4, and Raman spectra were obtained using a 785 nm light source. The Raman spectrum of rhodamine 6G was observed at 623 cm -1 There was a significant increase in the concentration of mercury ions, which was 375% higher than that of the blank sample. The mercury ion concentration was calculated by the standard curve to be 0.95×10 -12 mol / L. The performance of the quaternary ammonium xylan coated mercury ion detection paper-based chip M4 remained unchanged after being horizontally worn 50 times with a 100 g weight.

[0069] Comparative Example 1

[0070] (1) 20 g of dried dewaxed bagasse raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and a 1.5 wt% sodium hydroxide solution was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 60°C for 3 h, and the extract was precipitated with alcohol to obtain alkali-extracted bagasse xylan. The prepared xylan was dissolved in ultrapure water to prepare a 10 wt% xylan solution, 3 mL of the xylan solution was added to 12 mL of a tetrachloroauric acid trihydrate aqueous solution containing 5 mg of tetrachloroauric acid trihydrate, and the mixture was reacted in a 60 ℃ constant temperature water bath with stirring for 30 min at a stirring speed of 300 rpm to obtain a xylan / gold nanoparticle dispersion. After the reaction, 100 μL of a 10 mmol / L 4-thiobenzoic acid (4-MBA) ethanol solution was added to the xylan / gold nanoparticle dispersion and treated at 30 ℃ for 20 min to obtain a xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0071] (2) The xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was coated on the surface of 5 cm×5 cm filter paper by roller coating, and the two sides were coated 10 times respectively. After each coating, the filter paper was placed in a 45°C oven for 20 min. After the coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare the xylan / gold nanoparticles / beacon molecule composite coating paper.

[0072] (3) Mix 2 mL of 0.2 wt% sodium hydroxide and 0.6 mL of 0.1 mol / L silver nitrate solution, then add ammonia water until the precipitate disappears to prepare Tollens reagent. Place the xylan / gold nanoparticle / beacon molecule composite coating paper prepared in step (2) into the Tollens reagent and react at 60°C for 45 minutes. After the reaction, place the paper in a vacuum drying oven at 50°C for 12 hours to obtain the xylan-coated mercury ion detection paper-based chip M1-0. The effective loading amount of the xylan / gold nanoparticle / Raman beacon molecule composite coating material is 8.36 g / m 2 .

[0073] The configured 1×10 -15 10 μL of mol / L mercury ion solution was dropped onto the paper-based chip M1-0, and the Raman spectrum was collected using a 633 nm light source. In the Raman spectrum of 4-MBA, 1589 cm -1 No enhancement effect was observed. The performance of paper-based chip M1-0 remained unchanged after being horizontally abraded 50 times with a 100 g weight.

[0074] Comparative Example 2

[0075] (1) 20 g of dried dewaxed hardwood raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and anhydrous dimethyl sulfoxide was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 80°C for 7 h, and the extract was precipitated with alcohol to obtain alkali-extracted hardwood xylan.

[0076] A certain amount of xylan was dissolved in ultrapure water to prepare a 20 wt% xylan solution. 5 mL of the xylan solution was added to 10 mL of tetrachloroauric acid trihydrate aqueous solution containing 25 mg of tetrachloroauric acid trihydrate, and the mixture was reacted in a 75 ℃ constant temperature water bath with stirring for 20 min at a stirring speed of 300 rpm to obtain a xylan / gold nanoparticle dispersion. After the reaction, 200 μL of 30 mmol / L crystal violet ethanol solution was added to the above xylan / gold nanoparticle dispersion and treated at 40 ℃ for 40 min to obtain a xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0077] (2) The xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was coated on the surface of 5 cm×5 cm filter paper by spin coating, and the two sides were coated 10 times respectively. After each coating, the filter paper was placed in a 50°C oven for 25 min. After the coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare the xylan / gold nanoparticles / beacon molecule composite coating paper.

[0078] (3) Mix 5 mL of 0.3 wt% sodium hydroxide and 1.5 mL of 0.05 mol / L silver nitrate solution, then add ammonia water until the precipitate disappears to prepare Tollens reagent. Place the xylan / gold nanoparticle / beacon molecule composite coating paper prepared in step (2) into the Tollens reagent and react at 80°C for 40 minutes. After the reaction, place the paper in a vacuum drying oven at 50°C for 12 hours to obtain the xylan-coated mercury ion detection paper-based chip M3-0. The xylan / gold nanoparticle / Raman beacon molecule composite coating material has a loading capacity of 9.29 g / m 2 .

[0079] The configured 1.0×10 -10 10 μL of mol / L mercury ion solution was dropped onto the paper-based chip and Raman spectra were taken using a 633 nm light source. In the Raman spectrum of crystal violet, 1615 cm -1 No obvious enhancement was observed.

[0080] Comparative Example 3

[0081] (1) 20 g of dewaxed corncob raw material was placed in a conical flask, and a 2.0 wt% sodium chlorite solution was added at a solid-liquid ratio of 1:25 (g / mL) to perform delignification treatment to obtain holocellulose. The holocellulose was placed in a conical flask, and a 3.5 wt% sodium hydroxide solution was added at a solid-liquid ratio of 1:15 (g / mL). The holocellulose was extracted at 80°C for 3 h, and the extract was precipitated with alcohol to obtain alkali-extracted corncob xylan.

[0082] A certain amount of xylan was dissolved in ultrapure water to prepare a 40 wt% xylan solution. 5 mL of the xylan solution was added to 10 mL of tetrachloroauric acid trihydrate aqueous solution containing 40 mg of tetrachloroauric acid trihydrate. The mixture was reacted in a constant temperature water bath at 80 °C for 40 min with a stirring speed of 300 rpm to obtain a xylan / gold nanoparticle dispersion. After the reaction, 150 μL of rhodamine 6G (R6G) ethanol solution with a concentration of 25 mmol / L was added to the above xylan / gold nanoparticle dispersion and treated at 55 °C for 60 min to obtain a xylan / gold nanoparticle / Raman beacon molecule composite coating material.

[0083] (2) The xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared above was loaded on the surface of 5 cm×5 cm filter paper by chemical vapor deposition. This process was repeated 5 times. After each treatment, the filter paper was placed in a 45°C oven for 15 min. After coating, the filter paper was placed in a vacuum drying oven for 24 h to prepare xylan / gold nanoparticles / beacon molecule composite coating paper.

[0084] (3) Mix 3.5 mL of 0.2 wt% sodium hydroxide and 1.2 mL of 0.01 mol / L silver nitrate solution, then add ammonia water until the precipitate disappears to prepare Tollens reagent. Place the xylan / gold nanoparticle / beacon molecule composite coating paper prepared in step (2) into the Tollens reagent and react at 75°C for 50 minutes. After the reaction, place the paper in a vacuum drying oven at 50°C for 24 hours to obtain the xylan-coated mercury ion detection paper-based chip M4-0. The effective loading amount of the xylan / gold nanoparticle / Raman beacon molecule composite coating material is 8.92 g / m 2 .

[0085] The configured 1.0×10 -12 50 μL of mol / L mercury ion solution was dropped onto the paper-based chip M4-0, and Raman spectra were obtained using a 785 nm light source. In the Raman spectrum of rhodamine 6G, 623 cm -1 No obvious enhancement can be observed.

[0086] Figure 1 The carbon NMR spectra of the quaternized xylan and the unmodified xylan used in Example 1, wherein 56.7 ppm is attributed to the quaternary ammonium group signal; 64.9 ppm is -C-OH resonance; and 68.2 ppm is the -CN resonance signal. Compared with the original xylan spectrum, the signals are obvious, which indicates that the modification is successful.

[0087] Figure 2This is the ultraviolet spectrum of the gold nanoparticle dispersion obtained by reducing quaternary ammonium xylan in Examples 1-4. The unique surface plasmon resonance peak of AuNPs was observed at 524 nm, indicating that the quaternary ammonium xylan successfully reduced chloroauric acid to obtain gold nanoparticles. M1~M4 in the figure represent Examples 1~4 respectively.

[0088] Figure 3 The SEM image and EDS image of the quaternary ammonium xylan coated mercury ion detection paper-based chip prepared after the quaternary ammonium xylan / gold nanoparticle dispersion in Example 1 was treated with Tollens reagent. It can be seen in the figure that the gold and silver nanoparticles are evenly distributed on the surface of the paper, and it shows that the quaternary ammonium xylan plays a role in dispersing and stabilizing the gold / silver nanoparticles; indicating that the quaternary ammonium xylan coated mercury ion detection paper-based chip was successfully prepared.

[0089] Figure 4 1.0×10 -15 Raman spectra of mol / L mercury ion solution and M1 and M1-0 blank controls. The M1 sample has a concentration of 1598 cm -1 The characteristic peak of 4-thiobenzoic acid (4-MBA) at 1598 cm was enhanced by 59%, indicating that the quaternary ammonium xylan-coated mercury ion detection paper-based chip was successfully prepared. -1 There is no enhancement in the intensity of the characteristic peak at , indicating that the quaternary ammonium modification of xylan is a necessary step for high-sensitivity detection of mercury ions.

[0090] Figure 5 The Raman spectra of mercury ion detection paper chip M1 with quaternary ammonium xylan coating after adding different concentrations of mercury ion solutions at 1589 cm -1 1.0×10 -5 ~10 -15 mol / L mercury ion solution, and fitted the fitting curve of the peak intensity changing with the mercury ion concentration. It can be observed that with the increase of mercury ion concentration, 1589cm -1 The peak intensity at is enhanced, and the fitting result is Y=-5117.81432X+61757.3011, R 2 =0.90802. This equation can be used to quantitatively analyze the concentration of mercury ions.

[0091] Figure 6 Different metal ion solutions (all with a concentration of 1.0×10 -12 mol / L) after Raman spectrum at 1589cm -1 It can be observed that other metal ions have no effect on the Raman spectrum.

[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a quaternized xylan-coated mercury ion detection paper-based chip, characterized in that: The following steps are involved: (1) A quaternary ammonium xylan solution and an aqueous solution of tetrachloroauric acid trihydrate are mixed and reacted at 40-90°C for 10-80 min to obtain a quaternary ammonium xylan / gold nanoparticle dispersion; then a Raman beacon molecule is added to the quaternary ammonium xylan / gold nanoparticle dispersion and reacted at 30-60°C for 10-60 min to obtain a quaternary ammonium xylan / gold nanoparticle / Raman beacon molecule composite coating material; The mass ratio of the tetrachloroauric acid trihydrate to the quaternary ammonium xylan in the quaternary ammonium xylan solution is 5-40 mg: 0.1-2 g; the mass ratio of the Raman beacon molecule to the tetrachloroauric acid trihydrate is 0.2-5: 5-40; (2) coating the quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material prepared in step (1) onto the surface of paper to prepare quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating paper; (3) immersing the quaternary ammonium xylan / gold nanoparticle / beacon molecule composite coated paper prepared in step (2) into Tollens reagent for reaction, taking out and drying, thereby obtaining a quaternary ammonium xylan coated mercury ion detection paper-based chip; The quaternized xylan in the quaternized xylan solution in step (1) is prepared by the following steps: reacting xylan and a quaternizing agent at 30-60°C and a pH of 8-12 for 12-24 hours to obtain quaternized xylan; the quaternizing agent is one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, 2, 3-epoxypropyltrimethylammonium chloride, dodecyltrimethylammonium chloride, and tetrabutylammonium chloride; and the molar ratio of the xylan to the quaternizing agent is 1:1-1:1.

5.

2. The preparation method according to claim 1, characterized in that: The Raman beacon molecule in step (1) is at least one of 4-thiobenzoic acid, crystal violet and rhodamine 6G.

3. The preparation method according to claim 1, characterized in that: The coating method in step (2) is at least one of roller coating, spin coating, spray coating, dipping, and chemical vapor deposition; In step (2), the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coating material is applied to the surface of the paper by double-sided coating, 5 to 10 times on each side; the effective loading amount of the quaternary ammonium xylan / gold nanoparticles / Raman beacon molecule composite coating material on the paper is 5 to 10 g / m 2 ; After each coating treatment in step (2), the coated paper is dried in an oven for 10 to 30 minutes before the next coating treatment. After all coating treatments are completed, the paper is placed in a vacuum drying oven for 12 to 24 hours.

4. The preparation method according to claim 1, characterized in that: The specific steps of step (3) include: placing the quaternary ammonium xylan / gold nanoparticles / beacon molecule composite coated paper into Tollens reagent at 50-80°C for 30-60 min, and then vacuum drying the treated test paper at 45-55°C for 12-24 h.

5. A quaternary ammonium xylan coated mercury ion detection paper-based chip prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the quaternized xylan coated mercury ion detection paper-based chip according to claim 5 in detecting mercury ions in a solution.

Citation Information

Patent Citations

  • Quaternization xylan, preparation method via semi-dry process and application of quaternization xylan

    CN103214598A

  • Xylan-based auxiliary rapid detection test paper for organic pollutants as well as preparation method and application of xylan-based auxiliary rapid detection test paper

    CN115629055A

  • Paper-Based Surface-Enhanced Raman Scattering Substrate, and Preparation Method Therefor

    US20180080878A1